完全胸腔镜下解剖性肺段切除术治疗早期肺癌的体会 (Zhongguo Fei Ai Za Zhi, 2018)
BACKGROUND AND OBJECTIVE: Segmentectomy can retains more healthy lung tissue than lobectomy, but it remains controversial in oncology for early stage lung cancer. The aim of this study is to discuss the problems of video-assisted thoracic surgery (VATS) segmentectomy in early stage lung cancer, by analyzing the clinical and pathological data of 35 cases and reviewing the literature. METHODS: There were 35 patients who received segmentectomy by complete video-assisted thoracic surgery, from May 2013 to July 2017, in single operation group in the Third Hospital of Peking University. We analyzed the patient's clinical and pathological data, intraoperative and postoperative complications, lymph node number and metastasis its situation, and compared postoperative pathology and preoperative computed tomography (CT) imaging type. In 35 cases of segmentectomy, there were 11 males and 24 females, with an average age of 57.7 years old. The lesions located in the right upper lobe were 8 cases, in the right lower lobe were 8 cases, in the left upper lobe were 13 cases, in the left lower lobe were 6 cases. The mean maximum diameter of CT imaging was 12.7 mm, and the largest diameter of hilar and mediastinal lymph nodes was less than 10 mm. 23 of them were ground glass predominating and 12 were solid components predominating. RESULTS: All 35 cases were successfully completed VATS anatomical segmentectomy. The average operation time was 153 minutes, the amount of bleeding was 51 mL. There were 10 cases of air leakage after operation, all of which were not more than 3 days. There was contralat-eral atelectasis in 1 case, chylothorax in 1 case. The average length of hospitalization was 6.1 days. There was no other complications outpatient related to surgery, in 30 days after discharge. The pathological changes were as follow, 2 cases of metastatic tumor, 8 cases of benign lung disease and 25 cases of primary lung cancer. In the 25 cases of primary lung cancer, there were 14 cases of invasive lung adenocarcinoma (7 cases were groundglassopacity (GGO) predominating in CT imaging), 4 cases of micro-invasive adenocarcinoma (3 cases were GGO predominating in CT imaging), 6 cases of adenocarcinoma in situ (all were pure GGO in CT imaging), 1 case of lung squamous cell carcinoma (mainly composed of solid in CT imaging). An average of 7.2 lymph nodes were removed in 25 cases of lung cancer, and all lymph nodes had no metastasis. CONCLUSION: VATS anatomical segmentectomy is technically safe and reliable, and the indications for lung cancer need to be strictly controlled. Its advantages still need to be confirmed by prospective randomized controlled trials.